Life table parameters of Tetranychus urticae (Trombidiformes: Tetranychidae) on four strawberry cultivars - Shimaa F. Fahim; Faten M. Momen; El-Sayed M. El-Saiedy (Persian Journal of Acarology)
The two-spotted spider mite, Tetranychus urticae Koch is one of the most important pests of strawberry plants worldwide. The present study compared the biology and life table parameters of T. urticae on four strawberry cultivars, including Wanter star, Markez, Fortona and 029 under laboratory conditions. Female developmental times showed a significant difference when recorded on tested cultivars, while such a difference was not observed for the male ones. The developmental time was significantly longer on Wanter star and Fortona in comparison with the others (P = 0.00). Females of T. urticae exhibited the shortest oviposition period and adult longevity on Fortona and Wanter star, while having the longest periods on 029 in this report (P = 0.00). The lowest fecundity and daily eggs laid by females were recorded on Wanter star. The highest rate of fertility was recorded on 029 as compared to other cultivars; therefore, Wanter star is introduced as a resistant cultivar against T. urticae infestation.